Nilai dan Pendidikan Nilai - Tatang M. Amirin (Jurnal Penelitian Pendidikan, 2012)
Abstract:There are several definitions about value, most of them define value as a principle, standard, orquality considered worthwhile or desirable. Value differs from moral, although both speak aboutgood and bad, right and wrong, should and shouldn’t. Moral is stronger than value; peopleusually judge others more strongly on morals than values. Value also differs from character.Character is the complex of mental and ethical traits marking and often individualizing a person,group, or nation. So to say, character education is not the same as value education. There arethree stages or periods of value development, i.e. the imprint period, the modeling period, andthe socialization period. The traditional model of values education has placed greater emphasison the content of values instead of on the valuer, the one choosing and acting on the values. Inthe humanistic model, however, there is a shift. The stress is from content- to process-based,values- to valuer-focused and teacher- to student-centred orientation. Socio-culturalenvironment is the great value educator for the children. Recently we need more moralisticmodels performed by public figures.